(untitled) (Journal of Asian Geography, 2026)
This study aims to analyse the influence of land use change on the formation of the Urban Heat Island (UHI) in Melaka between 2020 and 2024. The UHI phenomenon has become increasingly evident due to rapid development and urbanisation, particularly in Melaka Tengah. Land use data were obtained from PLANMalaysia, while Land Surface Temperature (LST) data were derived from Landsat satellite imagery using the Google Earth Engine (GEE) platform. The analysis shows that built-up areas, such as buildings and urban infrastructure, contribute most significantly to the increase in surface temperature, with consistent growth in spatial extent. In contrast, forest areas, water bodies, and agricultural land have experienced noticeable reductions, thereby decreasing the natural capacity for temperature regulation. Melaka Tengah recorded the most significant UHI effect, while Alor Gajah and Jasin exhibited lower intensity due to the presence of more green and agricultural areas. This study highlights the importance of sustainable land use planning, including the expansion of urban green spaces, protection of forests and water bodies, and balanced development strategies to mitigate future UHI impacts.